2000
DOI: 10.1086/309061
|View full text |Cite
|
Sign up to set email alerts
|

Beaming, Baryon Loading, and the Synchrotron Self‐Compton Component in Gamma‐Ray Bursts

Abstract: We present detailed calculations of nonthermal synchrotron and synchrotron self-Compton (SSC) spectra radiated by blast waves that are energized by interactions with a uniform surrounding medium. Radio, optical, X-ray and gamma-ray light curves and spectral indices are calculated for a standard parameter set that yields hard GRB spectra during the prompt emission phase. Because no lateral spreading of the blast-wave is assumed, the calculated temporal breaks represent the sharpest breaks possible from collimat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
196
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(205 citation statements)
references
References 59 publications
6
196
3
Order By: Relevance
“…The major difference between the fits derived to GRB spectra during the prompt and afterglow phases is thus the stronger value of field at later times. Other arguments that the magnetic field evolves to its equipartition value following the prompt phase are given by Dermer et al (2000b). As can be seen from Figure 1, the relative timescales for photomeson production in the external shock model usually dominate the other processes and approach or exceed unity for the highest energy protons during the afterglow phase.…”
Section: Energy-loss Timescales For High-energy Protonsmentioning
confidence: 98%
See 1 more Smart Citation
“…The major difference between the fits derived to GRB spectra during the prompt and afterglow phases is thus the stronger value of field at later times. Other arguments that the magnetic field evolves to its equipartition value following the prompt phase are given by Dermer et al (2000b). As can be seen from Figure 1, the relative timescales for photomeson production in the external shock model usually dominate the other processes and approach or exceed unity for the highest energy protons during the afterglow phase.…”
Section: Energy-loss Timescales For High-energy Protonsmentioning
confidence: 98%
“…Other than E 0 and p, Figure 1a employs the parameter set in Figure 1 of Dermer, Chiang, & Mitman (2000b), which was shown to give good fits to burst spectra during the gamma-ray luminous phase of GRBs (Chiang & Dermer 1999; there we used E 0 ¼ 10 54 ergs and p ¼ 2:5). The remaining parameters used in Figure 1a are À 0 ¼ 300, n 0 ¼ 100 cm À3 , e B ¼ 10 À4 , and e e ¼ 0:5.…”
Section: Energy-loss Timescales For High-energy Protonsmentioning
confidence: 99%
“…In general, the photons produced by synchrotron radiation can be scattered by the relativistic electrons. Therefore, an inverse Compton process or synchrotron self-Compton (SSC) process is proposed naturally to explain the GRB emission above the GeV band (Mészáros et al 1993;Dermer et al 2000;Wang et al 2001;Zhang & Mészáros 2001;Granot & Guetta 2003;Fan et al 2008;Zou et al 2009;Corsi et al 2010). In particular, the possibility was suggested that the photons from X-ray flares can be scattered to the GeV band by those relativistic electrons (Wang et al 2006;Galli & Guetta 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The Tupi experiment is in the process of expansion, and within the next six months we are able to increase the number of telescopes to fourteen, increasing in 85% the field of view of the Tupi experiment. Our objective is to take advantage of our location inside the anomaly to detect gamma ray burst in the range of GeV to TeV, because there are theoretical models that predict GRBs in this energy region [15][16][17], with strong astrophysical implications. Naturally, we will continue to study solar transient phenomena, and monitoring the precipitation of particles.…”
mentioning
confidence: 99%